Observational Assessment of Blood Pressure Goal Achievement in Patients on Antihypertensive Therapy in Urban Pakistan: Results of ACTION Registry - Syed Arshad Sabir; Bashir Hanif, Aziz-Ur-Rehman, Saleem Ullah, Nadeem Hayat Mallick, Fayyaz Hussain Shah (Journal of Rawalpindi Medical College, 2016)
Background: To assess the proportion of Pakistani patients achieving blood pressure goal while on existing antihypertensive therapy and reasons for not achieving BP goal. Methods: This descriptive study was conducted in 60 centers across 10 cities of Pakistan by simple random sampling. It was a national, multi-centre, noninterventional, cross-sectional, epidemiological disease registry. Patients, who were ≥15 years of age, on antihypertensive medications for ≥4 weeks and had taken a dose on the day of visit, were included. Investigators were randomly selected from a list of physicians within a given geographical territory (Urban) in major cities of Pakistan. Approximately 58% of the physicians were general practitioners and 42% were specialist such as medical internist and cardiologist. Reasons for not achieving BP goal was determined by assessing different variables. Changes made in BP management in patients not at BP goal and therapeutic regimens prescribed to patients at BP goal were also documented. Differences in the profile of patients according to the attainment of BP goal were analyzed using bi-variate analysis. A p <0.05 was considered significant. Results: Mean age of patients (n=1130) was 52.6 ± 11.9 years. Of them 49% were females. Mean duration of HTN was 6.1 (±6.2) years. Of 1130 patients, 23.80% achieved BP goal. In patients not achieving BP goal, history of sedentary lifestyle (60.27%), diabetes (42.97%), and dyslipidemia (40.30%) were identified as risk factors. Coronary artery disease (21.25%) was the most common comorbid condition. Lack of patient understanding on treatment importance (47.03%) was major reason for not achieving BP goal. Lifestyle modification (37.74%) and addition of another drug (37.74%) were recommended. Majority of patients at BP goal received angiotensinconverting enzyme inhibitors (36.05%). Conclusion: In Pakistan, only one in four patients taking antihypertensive medications and presenting to physicians achieves BP goal as per JNC VII guidelines. This has significantly improved as compared with previous survey. Lack of understanding of importance of BP treatment remains the major impediment in achieving better BP control